2018
DOI: 10.32890/mjli2018.15.2.8
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Know What is Happening in Whatsapp: A Case Study Investigating Pre-Service Teachers’ Online Activity

Abstract: Purpose - This study addresses the issue of investigating on how lecturers used WhatsApp in educational context and what are the pre-service teachers’ views when WhatsApp is used in teaching and learning activities. Methodology - A qualitative case study was conducted in this study. Two lecturers were interviewed individually to investigate the teaching approach integrated with the use of WhatsApp. Also, 12 pre-service teachers in two focus groups were interviewed to examine their views of using WhatsApp in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
3
17
1
3
Order By: Relevance
“…The main outcome of this study, the online learning effect, showed a statistically significant increase via the knowledge score. Annamalai [28] also found that online learning produced positive learning outcomes, making students more knowledgeable. This is in line with the finding that the participants' self-regulation was relatively high in the pretest, and there was a significant increase in learning flow after online learning.…”
Section: Discussionmentioning
confidence: 97%
“…The main outcome of this study, the online learning effect, showed a statistically significant increase via the knowledge score. Annamalai [28] also found that online learning produced positive learning outcomes, making students more knowledgeable. This is in line with the finding that the participants' self-regulation was relatively high in the pretest, and there was a significant increase in learning flow after online learning.…”
Section: Discussionmentioning
confidence: 97%
“…WhatsApp used as an online learning platform where it is a medium for communication and collaboration. Teachers and students can used the WhatsApp application current updated features in conducting the teaching and learning process creatively [47]. Moreover, [19] mentioned that WhatsApp application allowed students to deal with new information, create social networks, offered idea-sharing, and develop understanding and learning mutually in informal forms.…”
Section: Discussion On the Level Of Whatsapp Usage In Education Among Utm Studentsmentioning
confidence: 99%
“…Based on the findings, there was a strong, positive, and significant correlation that exists between the level of WhatsApp usage in education and the level of communication skills by utilizing WhatsApp application for educational purposes among UTM students. With the advancement of technology, students gained the essential communication skills required in 21st-century learning [47,54]. By utilizing WhatsApp application to its maximum potential and the ability to extend the learning in different situations and environment, it helps students to use the technology without boundaries and limits [47].…”
Section: Discussion On the Correlation Between The Level Of Whatsapp Usage In Education And The Level Of Communication Skills By Utilizinmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance learning carried out is lacking in terms of interaction, teachers cannot directly monitor the learning process and limited ability to receive material delivered online with instant messaging applications such as WhatsApp media [5]. This is because distance learning is still considered no better than conventional direct learning, students cannot ask the teacher directly if there is material that is not understood through virtual explanations.…”
Section: Introductionmentioning
confidence: 99%